Peningkatan kualitas pembelajaran di sekolah pedesaan: Peran inovasi dalam membuka akses pendidikan berkualitas - Nabilah, Nur Rahma (Maliki Interdisciplinary Journal, 2025)
Enhancing the quality of learning in rural schools poses a significant challenge in the pursuit of educational equity in Indonesia. Although factors such as limited facilities, insufficient human resources, and restricted access to information hinder progress, innovative approaches to the learning process can be instrumental in providing access to quality education in remote areas. This article seeks to explore the impact of innovation on improving learning outcomes in rural schools. Utilizing a qualitative research methodology, we conducted case studies of several rural schools that have adopted innovative learning strategies. The findings reveal that the integration of learning technology, project-based learning methods, and increased community engagement significantly boosts students’ motivation, enhances teaching quality, and fosters greater participation in education from the community. Furthermore, supportive policies that promote teacher professionalism and leverage local resources are crucial for the successful implementation of these innovations. Overall, the results indicate that innovations—whether they relate to teaching methods, technological tools, or community involvement—play a vital role in enhancing the quality of education in rural schools. It is essential to continue promoting such innovative strategies to ensure equitable access to quality education across all regions, including those that are rural.